Direct laser writing of synthetic poly(amino acid) hydrogels and poly(ethylene glycol) diacrylates by two-photon polymerization - Käpylä, Elli; Sedlačík, Tomáš; Aydogan, Dogu Baran; Viitanen, Jouko; Rypáček, František; Kellomäki, Minna (Materials science & engineering. C, Materials for biological applications, 2014)
The additive manufacturing technique of direct laser writing by two-photon polymerization (2PP-DLW) enables the fabrication of three-dimensional microstructures with superior accuracy and flexibility. When combined with biomimetic hydrogel materials, 2PP-DLW can be used to recreate the microarchitectures of the extracellular matrix. However, there are currently only a limited number of hydrogels applicable for 2PP-DLW. In order to widen the selection of synthetic biodegradable hydrogels, in this work we studied the 2PP-DLW of methacryloylated and acryloylated poly(α-amino acid)s (poly(AA)s). The performance of these materials was compared to widely used poly(ethylene glycol) diacrylates (PEGdas) in terms of polymerization and damage thresholds, voxel size, line width, post-polymerization swelling and deformation. We found that both methacryloylated and acryloylated poly(AA) hydrogels are suitable to 2PP-DLW with a wider processing window than PEGdas. The poly(AA) with the highest degree of acryloylation showed the greatest potential for 3D microfabrication.
Keywords: Polyethylene Glycols; polymerizace; polyethylenglykoly; mikroskopie elektronová rastrovací; Amino Acids; Lasers; Hydrogels; aminokyseliny; fotony; Microscopy, Electron, Scanning; Photons; lasery; Polymerization; hydrogely